2004
DOI: 10.1186/1741-7015-2-13
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the incidence of schizophrenia: the distribution of rates and the influence of sex, urbanicity, migrant status and methodology

Abstract: Background: Understanding variations in the incidence of schizophrenia is a crucial step in unravelling the aetiology of this group of disorders. The aims of this review are to systematically identify studies related to the incidence of schizophrenia, to describe the key features of these studies, and to explore the distribution of rates derived from these studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

54
620
8
34

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 875 publications
(716 citation statements)
references
References 169 publications
54
620
8
34
Order By: Relevance
“…These include the findings that NAP has a median age-of-onset in the late teens or early twenties that is somewhat earlier among men than women (Jablensky et al 1992), that NAP is significantly related to disadvantaged social status (Jablensky 2000), that NAP is highly comorbid with a wide range of other mental disorders and substance use disorders (Murray et al 2002), that NAP is associated with substantial impairment in all areas of life (Jablensky et al 1980), and that the vast majority of people with NAP are in contact with the treatment system (Sartorius et al 1986). We also found a somewhat higher relative-odds of NAP among men than women (1.6), which is consistent with a modest, but statistically significant, elevation among men compared to women found in meta-analysis of incidence studies (McGrath et al 2004).…”
Section: Discussionsupporting
confidence: 78%
“…These include the findings that NAP has a median age-of-onset in the late teens or early twenties that is somewhat earlier among men than women (Jablensky et al 1992), that NAP is significantly related to disadvantaged social status (Jablensky 2000), that NAP is highly comorbid with a wide range of other mental disorders and substance use disorders (Murray et al 2002), that NAP is associated with substantial impairment in all areas of life (Jablensky et al 1980), and that the vast majority of people with NAP are in contact with the treatment system (Sartorius et al 1986). We also found a somewhat higher relative-odds of NAP among men than women (1.6), which is consistent with a modest, but statistically significant, elevation among men compared to women found in meta-analysis of incidence studies (McGrath et al 2004).…”
Section: Discussionsupporting
confidence: 78%
“…It was expected to find differences in FAAH expression between genders, as its activity is regulated by sexual hormones (mainly progesterone and estrogens; Battista et al, 2012;Lazzarin et al, 2004). Knowing that males have a higher lifetime risk of developing schizophrenia (with a male-female relative risk of about 1.4 (Aleman et al, 2003;McGrath et al, 2004)), the different FAAH expression found in this study could be one of the factors involved in these risk differences between genders.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent, extensive review of worldwide incidence rate, it was found that males have significantly higher incidence rate than females. 52 The males have younger age of onset than the females. 53 Sex-specific associations with schizophrenia have been reported for the catechol omethyltransferase gene 38 and several other genes.…”
Section: Discussionmentioning
confidence: 99%